EXCAVATIONS OF A NEW OBJECT OF SASANIAN FORTIFICATION AT THE RIVER RUBAS IN 2014 - Gmyra, L B; Saidov, V A; Abdulaev, A M; Sausev, K B; Magomedov, U A; Kuzeeva, Z Z (History, Archeology and Ethnography of the Caucasus, 2015)
-